Implementation of Human Resource Fulfillment Policy Based on Workload Indicator Staff Need (WISN) and Influencing Factors - Muhajir Muhajir; Nurwalmi Nurwalmi; Darwis Durahim; Syamsuddin Syamsuddin (Universitas Kristen Indonesia Toraja, 2024)
This research investigates the challenges in implementing the human resource (HR) fulfillment policy at the Regional General Hospital of Prof. Dr. H.M. Anwar Makkatutu, focusing on the application of the Workload Indicator Staff Need (WISN) method and the analysis of crucial influencing factors. Employing a mixed-methods research design with a cross-sectional approach, this study involved 15 heads of departments as participants. Data were collected through interviews and document analysis. The research findings revealed that several work units experienced a high workload and staff shortages. The suboptimal implementation of WISN was attributed to an incomplete identification of productive activities, the use of estimated data, and the absence of official policy guidelines regarding HR calculation. Additionally, factors such as connection-based recruitment practices, political dynamics, and internal interests also impacted HR fulfillment. Overall, this research concludes that the implementation of the HR fulfillment policy using WISN at the Regional General Hospital of Prof. Dr. H.M. Anwar Makkatutu has not reached its full potential due to technical constraints in the application of WISN and the strong influence of organizational contextual factors. These research findings are relevant not only to the hospital context in Indonesia but also provide important insights for other countries facing similar issues in health HR management, particularly regarding the influence of non-technical factors and data validity in the implementation of the WISN method.